Dermoscopic features of hypertrophic scars and keloids - Hayyawi, Huda Hadi; Al-Hamamy , Hayder R (Journal of Pakistan Association of Dermatologists, 2023)
Background: Dermoscopy is a noninvasive diagnostic technique that permits the visualization of morphologic features beneath the skin surface, thus representing a link between macroscopic clinical dermatology and microscopic dermatopathology. Its aid in the diagnosis of many inflammatory and skin diseases. Aim of the study: The present study was conducted to outline dermoscopic features that help to differentiate between keloids and hypertrophic scars. Patients and Methods: The study is an observational cross-sectional study conducted at the Center of Dermatology/ Medical City Teaching Hospital, Baghdad. The study was carried out during a period extending from December 1st 2020 to August 1st 2021 on a convenient sample of 95 patients; (33) with hypertrophic scars and (62) with keloids. Full history and clinical examination were done for each patient. Clinical photos were captured by using an iPhone 8 (12 megapixels) camera. Dermoscopic study was done using Handyscope classic from Fotofinder, Results: following features were noted pigment color in keloids was pink (43.5%), while in hypertrophic scar it was brown (69.7%) (p value =0.001). The most frequent vessel shape in keloids was arborizing (46.8%), arborizing/ linear (14.5%).While in hypertrophic scars the most frequent vessel shape was dotted (39.4%), followed by linear (21.2%), (p value = 0.001). Conclusions: The vessels shape and distribution as well as the pigment was different in keloids compared to hypertrophic scars (statistically significant) which help to differentiate the 2 in clinically suspicious lesions.